A Performance Comparison of XBEE S2 Module and ESP8266 (12E) Module on Air Quality Monitoring System - Erwanto, Ricky Hastomo; Arrofiq, Muhammad (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2020)
The development of wireless sensor network (WSN) technology has progressed very rapidly. These developments also triggered the development of wireless modules used in WSN. Xbee and ESP8266 are wireless modules that are often used to design wireless sensor networks. Xbee uses the IEEE 802.15.4 standard while ESP8266 uses the IEEE 802.11 b / g / n standard. In this research will be comparison of wireless modules between Xbee and ESP8266 to test the performance of the wireless module. Comparison is performed by testing the value of throughput, delay packet, and packet lost. The test will be applied to the air quality monitoring system using the MQ135 sensor. The result of the research is the comparison of parameters tested from both wireless modules.